Generalized Resolvents of Symmetric Relations Generated on Semi-Axis by a Differential Expression and a Nonnegative Operator Function - Bruk, V.M. (Журнал математической физики, анализа, геометрии, 2006)
Generalized resolvents of a minimal symmetric relation generated on the semi-axis by a formally selfadjoint di erential expression and a nonnegative operator function are described.